Selection and Evaluation of Reference Genes for qRT-PCR in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Shipeng Han; Qiuju Qin; Da Wang; Yayuan Zhou; Yunzhuan He (Insects, 2021)
As an accurate and convenient technique, the qRT-PCR is always used in the quantitative expression analysis of functional genes. Normalization of the data relies on stable reference genes. The fall armyworm Spodoptera frugiperda (J. E. Smith) is an important invasive and migratory pest that seriously threatens corn production around the world. In this paper, we selected 10 candidate reference genes (18S, AK, RPL10, RPS24, 28S, SOD, ATP, GAPDH, ACT, and a-TUB) and determined their expression levels under different conditions (different developmental stages, various tissues, mating status, hormones, diets, and temperatures). Subsequently, the stability of reference genes was evaluated by four algorithms (Delta Ct method, geNorm, NormFinder, BestKeeper). The optimal combination of reference genes for each treatment was obtained by geNorm. Finally, the comprehensive ranks were determined by the online tool RefFinder. Results showed that the most stable reference genes were SOD, RPL10, and RPS24 for developmental stages, α-TUB, RPL10, and ATP for different tissues, AK, RPL10, and 18S for mating status, 18S and AK under hormone treatment, 18S, RPL10, and SOD under diet treatment, RPL10, 18S, and RPS24 under temperature treatment. This study confirmed recent data on a few reference genes and provided an evaluation of a number of additional reference genes of S. frugiperda under various conditions.